POSISI INDONESIA DALAM PERDAGANGAN KAKAO INTERNASIONAL: UPAYA PENINGKATAN DAYA SAING EKSPOR KAKAO INDONESIA - , DEWI NATALIA GINTING MUNTHE ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Globalization and trade liberalization will create a market which is considered more efficient because it will refer to the free trade system. Economic globalization resulted in a growing number of countries in the world who are directly involved in international trade activities. Cocoa Indonesia has good potential and bright prospects in international trade as the capital of Indonesia. This is because Indonesia is the third largest cocoa producer in the world after the Ivory Coast and Ghana as well as the most significant supplier of cocoa beans in East Asia. High competitiveness in various fields is one important factor in international trade. Market their products abroad are very competitive. So the ability to develop into important export commodity. In the global value chain analysis, this can be done through governance and upgrading in every aspect of the production chain. This is also true in the international cocoa trade in Indonesia that have a high competitiveness in international trade.